Case Report: Use of Amniotic Membrane for Tectonic Repair of Peripheral Ulcerative Keratitis With Corneal Perforation - Eslami, Maryam; Benito-Pascual, Blanca; Goolam, Saadiah; Trinh, Tanya; Moloney, Greg (Frontiers in Medicine, 2022)
Purpose: To provide a perspective and surgical video demonstration of peripheral corneal ulceration and perforation managed with multilayered amniotic membrane transplantation. Case Reports: Case 1 describes a 48-year-old female with progressive redness and pain, and an inferonasal corneal thinning and perforation in the left eye from peripheral ulcerative keratitis. She underwent conjunctival recession with amniotic membrane inlay and onlay (Sandwich technique) transplantation (Surgical Video Attached). The amniotic membrane integrated well, and her Snellen visual acuity improved from 6/21 preoperatively to 6/9 at 3 months post op. Case 2 describes a 78-year-old male with redness and pain with temporal corneal thinning bilaterally and perforation in the right eye from peripheral ulcerative keratitis. Both eyes underwent similar surgical intervention with smooth integration of the amniotic membrane in the cornea and improvement in the visual acuity. Both patients were also started on systemic immunosuppression in collaboration with the rheumatology team. Conclusion: We report successful use of multilayered amniotic membrane transplantation for the treatment of corneal ulceration and perforation. The authors believe the simplicity of the surgical technique, easier access to amniotic membrane tissue, and lower induced post operative astigmatism all provide advantages over alternative treatment modalities.